PERAN STRATEGIS MAHASISWA PPL DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN MELALUI PENDEKATAN RELIGIUSITAS DAN LITERASI EKOLOGIS - Raudlatun; Dimas Arifudin Affandi; Ageng Pangestu; Gilang Ramadani; Wahyu Rahman; Faizatul Mufliha; Nur Fadhilah Putri Ramadhani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the strategic role of student teachers in the Teaching Practicum Program (PPL) in enhancing learning effectiveness through the integration of religiosity and ecological literacy approaches in Islamic senior secondary education. The research is grounded in the growing need to strengthen spiritual character and environmental awareness as foundations for meaningful and sustainable learning. The objective is to analyze how student teachers design, implement, and evaluate instructional practices that incorporate religious habituation and ecological literacy programs to improve student engagement and learning outcomes. A descriptive qualitative approach was employed, utilizing participatory observation, in-depth interviews, and documentation. The participants included student teachers, mentor teachers, and students. Data were analyzed systematically through data reduction, display, and conclusion drawing. The findings indicate that integrating religious practices such as daily worship routines and value-based reflection and ecological literacy activities, including environmental projects and school cleanliness programs, significantly enhance students’ discipline, motivation, and active participation. This study contributes theoretically to the development of character- and sustainability-based learning models and offers practical implications for educational institutions in optimizing the transformative role of student teachers in fostering holistic and contextual learning environments.